PEMBELAJARAN BERBASIS STEM DALAM PERKULIAHAN KALKULUS DI PERGURUAN TINGGI - Khairani Khairani; Mukhni Mukhni; Faizah Qurrata Aini (Universitas Islam Nusantara, 2018)
Calculus is a must course of many major in higher education. It caused by calculus has a role as basic foundation of many theories and its application is used in many aspects of various majors. However, many students had difficulty to undersatand calculus course. Its difficulty was caused by calculus course could not been integrated with topics that was learned in each of majors. Solution of that problem is to integrated topics from various majors in calculus course and it can be done with STEM learning. STEM learning integrates science aspect (S), technology aspect (T), engineering aspect (E), and mathematics aspect (M) in learning process so it can makes calculus course to be more realistic so students can easily understand it.